2020
DOI: 10.1186/s42269-020-00424-7
|View full text |Cite
|
Sign up to set email alerts
|

Resistance against phomopsis leaf blight disease induced by potassium salts in strawberry plants

Abstract: Background Growing interest of strawberry cultivation in Egypt necessitates more efforts towards its severe phomopsis leaf blight disease caused by Phomopsis obscurans. Synthetic fungicides could control this fungus but due to their critical impact on human beings and the environment, we are in dire need of safe alternatives for its control. Therefore, the leverage of the potassium bicarbonate and dipotassium phosphate on P. obscurans suppression on strawberry plants was examined. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…White leaf spots (Figure 5D) (Cérès Agricole, Red Gold of Africa, Mbidjoro Sustainable Living Environment, and KAFFO Farm); leaf yellowing (Figure 5E) (Cérès Agricole, Red Gold of Africa, BIO Farm of Lolodorf, and Bafoussam Farm), and whitish down on the upper and lower leaf surfaces (Figure 6F) (KAFFO Farm) were also recorded. Melinda [27], Baroncelli [28], Abd-El-Kareem [29], and Mykhailenko [30] attribute these black spot symptoms to anthracnose caused by Colletotricum acutatum or Colletotricum gloeosporioides, or Cercospora fragariae, and purple blight caused by Diplocarpon earlianum, while the common leaf spots are caused by Mycosphaerella fragariae. On the other hand, white leaf spots are thought to be the result of Ramularia grevilleana attacks [29] [30].…”
Section: Diseases Identified In Strawberries In the Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…White leaf spots (Figure 5D) (Cérès Agricole, Red Gold of Africa, Mbidjoro Sustainable Living Environment, and KAFFO Farm); leaf yellowing (Figure 5E) (Cérès Agricole, Red Gold of Africa, BIO Farm of Lolodorf, and Bafoussam Farm), and whitish down on the upper and lower leaf surfaces (Figure 6F) (KAFFO Farm) were also recorded. Melinda [27], Baroncelli [28], Abd-El-Kareem [29], and Mykhailenko [30] attribute these black spot symptoms to anthracnose caused by Colletotricum acutatum or Colletotricum gloeosporioides, or Cercospora fragariae, and purple blight caused by Diplocarpon earlianum, while the common leaf spots are caused by Mycosphaerella fragariae. On the other hand, white leaf spots are thought to be the result of Ramularia grevilleana attacks [29] [30].…”
Section: Diseases Identified In Strawberries In the Fieldmentioning
confidence: 99%
“…The varieties of Fragaria x ananassa ("Madame Moutot", "Charlotte", "Elsanta", "Ruby gem", "Ostara", and "San Andreas") and Fragaria vesca ("Maestro" and "Mara des bois"), have presented the crown rot in some plants (Figure 7). Abd-El-Kareem [29], and Mykhailenko [30], attributed this symptom of crown rot to Phytophthora fragariae attacks.…”
Section: Diseases Identified In Strawberries In the Fieldmentioning
confidence: 99%
“…Phytophthora (red stele root rot) of strawberries is caused by two species of pseudo fungi of the Phytophthora genus (Abd- El-Kareem et al, 2020). The first one, Phytophthora fragariae Hickman, causes Phytophthora root rot or so-called « redness of the central root cylinder ».…”
Section: Red Stele Root Rot (Phytophthora Fragariae Hickman)mentioning
confidence: 99%
“…fungi are one of the most important pathogens, especially the semi-pathogenic fungus pythium aphanidermatum, which causes the disease of rotting seeds and roots and the fall of seedlings, as well as a wide family range and is known for the rapid destruction of the plant host and can stay in the soil for a long time on plant remains [7].chemical pesticides have been widely used to reduce losses caused by pathogens, as it has been found that excessive use of these pesticides causes an impact on human health and pollution of the environment [8] [9].therefore, researchers have turned to finding alternative environmentally friendly and safer methods that replace chemical pesticides, such as biological control methods using microbiology and the use of substances that induce resistance in the plant.trichoderma harzianum is one of the most widely used microorganisms in this field [10].the plant's defense system can also be induced as a response to environmental or biological stresses, depending mainly on its genetic and physiological characteristics. melatonin n -acetyl-5-methoxytyptamine derived from the amino acid tryptophan is one of the most important of these compounds [11].due to the interest of researchers in the resistance of plant pathogenic fungi using chemical compounds that do not have negative effects on living organisms, interest has increased in the use of sodium bicarbonate (NAHCO 3 ) to resist plant pathogenic fungi, as it works to reduce the growth of fungal pathogens as well as its use in the food industry [12] [13].therefore, this study aimed to identify the role of the biological control agent trichoderma harzianum., and inducing agents melatonin and sodium bicarbonate in the fight against the semi-pathogenic fungus pythium aphanidermatum, the cause of okra root rot disease, laboratory and field.…”
Section: Introductionmentioning
confidence: 99%